Superfine hollow CoSenanoneedle material as well as preparation method and application thereof
Ultrafine hollow CoSe2 nanoneedles were prepared by hydrothermal reaction, and the concentration of cobalt ions was controlled to form a flower-like multi-level structure, which solved the problem of insufficient catalytic performance of CoSe2 materials and achieved improved catalytic performance and stability for efficient water electrolysis to produce hydrogen.
Patent Information
- Application Number
- CN202511217417.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-28
- Publication Date
- 2025-12-02
AI Technical Summary
The catalytic performance of existing CoSe2 materials is limited by their small specific surface area, insufficient exposure of active sites, and the need to improve their conductivity.
Ultrafine hollow CoSe2 nanoneedles were prepared by hydrothermal reaction. The micromorphology of the catalyst was controlled by adjusting the cobalt ion concentration to form a flower-like multi-level structure. Combined with the conductivity of the nickel foam substrate and the high specific surface area of the hollow nanoneedles, in-situ growth was achieved.
It improves catalytic performance and cycle stability, reduces resistance and active site loss during electrocatalysis, and enhances electron conduction efficiency and material stability, making it suitable for hydrogen production via water electrolysis.
Smart Images

Figure CN121044548A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of hydrogen energy production, specifically to an ultrafine hollow CoSe2 nanoneedle material, its preparation method, and its application. Background Technology
[0002] With the increasing severity of the global energy crisis and environmental problems, the development of efficient, clean, and sustainable energy conversion and storage technologies has become one of the core topics in current scientific research. Among many new energy technologies, hydrogen energy is considered an ideal alternative to traditional fossil fuels due to its significant advantages such as high energy density and pollution-free combustion products. Electrolysis of water to produce hydrogen, as a green and environmentally friendly method, can convert renewable energy into chemical energy for storage; however, its widespread application is still limited by the efficiency, stability, and cost of electrocatalytic materials.
[0003] Currently, noble metal-based materials such as platinum and iridium exhibit excellent catalytic activity in the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) of water electrolysis, but their high cost and scarcity severely restrict their large-scale commercial application. Therefore, developing low-cost, highly active, and highly stable non-noble metal electrocatalysts has become key to solving this problem. Transition metal chalcogenides (TMCs) are considered one of the most promising alternative materials due to their unique electronic structure and catalytic properties. Among them, selenides such as CoSe2 and NiSe2 have attracted widespread attention from researchers due to their good electrical conductivity and catalytic activity.
[0004] CoSe2, a typical transition metal selenide, possesses abundant active sites in its crystal structure and exhibits hydrogen adsorption free energy close to that of noble metals, demonstrating good catalytic potential in both HER and OER processes. However, the catalytic performance of pure-phase CoSe2 materials is still limited by its small specific surface area, insufficient exposure of active sites, and the need to improve its conductivity. Summary of the Invention
[0005] The purpose of this invention is to provide an ultrafine hollow CoSe2 nanoneedle material, its preparation method and application, which can solve the problems of uneven morphology and low catalytic performance of CoSe2 material.
[0006] In one aspect of the present invention, a method for preparing ultrafine hollow CoSe2 nanoneedles is provided. According to an embodiment of the present invention, the method includes the following steps:
[0007] (1) Mix and dissolve cobalt nitrate, urea and ammonium fluoride, put in nickel foam, keep warm at 110-130 ℃ for 7-9 h, cool to room temperature, take out the reacted nickel foam, wash and dry to obtain the precursor;
[0008] (2) Mix and dissolve selenium powder and sodium hydroxide, keep warm at 190-210 ℃ for 7-9 h, and cool to room temperature to obtain an intermediate solution;
[0009] (3) Place the precursor in the intermediate solution and keep it at 140-160 °C for 7-9 h. After cooling to room temperature, take out the reacted nickel foam, clean and dry it to obtain the ultrafine hollow CoSe2 nanoneedle material.
[0010] The entire reaction process is as follows:
[0011] CO(NH2)2 + 3H2O → 2NH3·H2O + CO2↑ (1)
[0012] [Co(NH3)6] 2+ +1.3F − +0.7OH − → Co(OH) 0.7 F 1.3 ↓ + 4.7NH3↑ + 1.3NH4 + (2)
[0013] 3Se + 6NaOH → 2Na2Se + Na2SeO3 + 3H2O (3)
[0014] Na₂Se → 2Na⁺ + Se 2- (4)
[0015] Co(OH) 0.7 F 1.3 +2Se 2− +0.7H₂O→CoSe₂↓+0.7OH⁻ − +1.3F − +H2Se↑ (5)
[0016] Wherein, reaction formula (1) indicates that the NH3·H2O generated in step (1) creates alkaline conditions for the Co²⁺ precipitate; reaction formula (2) indicates [Co(NH3)6] 2+ It undergoes a displacement reaction with F⁻ and OH⁻ to generate a cobalt-based complex hydroxide fluoride precipitate, i.e., the precursor; reaction formula (3) indicates that in step (2), 0.3 g of selenium powder reacts with 2 g of sodium hydroxide to generate Na₂Se, which provides Se. 2- This provides a sufficient selenium source for the subsequent selenization reaction; reaction formula (4) indicates that Na2Se in step (3) dissociates into Se²⁻; reaction formula (5) indicates that the cobalt-based precursor (Co(OH)) 0.7 F 1.3 ) undergoes a substitution with Se²⁻ to generate CoSe2.
[0017] In addition, a method for preparing ultrafine hollow CoSe2 nanoneedles may also have the following additional technical features:
[0018] In an embodiment of the present invention, in step (1), the nickel foam is cleaned and dried before being placed in the container; the cleaning is performed by ultrasonic treatment with deionized water and alcohol respectively; the drying temperature is 50-70 ℃ and the drying time is 23-25 h; the length of the nickel foam is 3-5 cm, the width is 4-6 cm and the thickness is 10-12 μm.
[0019] In the embodiments of the present invention, the reactions are all carried out in a reaction vessel, and the nickel foam is perpendicular to the bottom of the reaction vessel.
[0020] In an embodiment of the present invention, in step (1), the molar ratio of cobalt nitrate, urea, and ammonium fluoride is 2.9-3.1 : 9.9-10.1 : 3.9-4.1. Cobalt nitrate provides Co. 2+ As a metallic center, urea provides OH- through hydrolysis. - and CO3 2- By regulating the alkaline environment, ammonium fluoride induces the directional growth of nanoneedles through selective adsorption. Ultimately, a cobalt-based precursor is generated in situ on the surface of nickel foam, laying the morphological and compositional foundation for the subsequent transformation into CoSe2 hollow nanoneedles.
[0021] In an embodiment of the present invention, in step (1), the cleaning is performed using anhydrous ethanol and deionized water, the drying temperature is 50-70 °C, and the drying time is 11-13 h.
[0022] In an embodiment of the present invention, in step (2), the mass ratio of selenium powder to sodium hydroxide is 0.2-0.4:1.9-2.1. The selenium powder, as the source of selenium, undergoes a disproportionation reaction in the strongly alkaline hydrothermal environment provided by sodium hydroxide, transforming into water-soluble Se²⁻ and SeO3²⁻, forming a highly active selenium source intermediate solution, which provides the necessary selenium ions for the selenization reaction of the cobalt-based precursor in step (3).
[0023] In an embodiment of the present invention, in step (3), the cleaning is performed using anhydrous ethanol and deionized water, the drying temperature is 50-70 °C, and the drying time is 11-13 h. Highly active Se²⁻ is provided by the reduction of SeO₃²⁻, which undergoes ion exchange and redox reactions with Co²⁺ in the cobalt-based precursor to generate CoSe₂; simultaneously, hollow nanoneedle structures are formed by template dissolution or selective etching within the precursor. The entire process is carried out under hydrothermal conditions, ultimately achieving in-situ growth of CoSe₂ hollow nanoneedles on the surface of nickel foam.
[0024] This invention obtains corresponding selenide electrode materials by selenizing precursor materials. Based on the conductivity and specific activity of cobalt-based precursors, the selenization reaction is carried out via Se... 2- Co in precursors 2+ Through substitution and bonding, it can be transformed into CoSe2 with high catalytic activity. This structure reduces the shedding of active components during electrocatalysis and improves the stability of the material.
[0025] This invention also proposes a method for controlling the microstructure of CoSe2 nanoneedle materials supported on nickel foam. This method modulates the microstructure of the catalyst by changing the concentration of cobalt ions. When the cobalt ion concentration is 1.9-2.1 mmol, the reaction rate between cobalt nitrate and urea is slow, resulting in fewer catalyst nuclei, sparse and short nanoneedles, and an indistinct hollow structure. As the concentration increases, the nucleation and growth rates balance, the nanoneedle density increases, the length becomes more uniform, and the hollow structure is intact. When the cobalt ion concentration is 3.9-4.1 mmol, excess cobalt ions cause rapid agglomeration of the precursor, leading to nanoneedle adhesion and a stacked structure, clogging pores and damaging hollow channels due to growth stress. When the cobalt ion concentration is 2.9-3.1 mmol, the in-situ growth of the precursor on the nickel foam surface is more uniform, and the nanoneedles form a root-like, tightly connected structure with the substrate.
[0026] In another aspect of the present invention, the present invention proposes a method for preparing the ultrafine hollow CoSe2 nanoneedle material described above.
[0027] In another aspect of the present invention, an electrode material is proposed, which is prepared by means of the ultrafine hollow CoSe2 nanoneedle material according to an embodiment of the present invention.
[0028] In another aspect of the present invention, a method for producing hydrogen by electrolysis of water is proposed, wherein, according to an embodiment of the present invention, the electrode material is used as the working electrode.
[0029] Compared with the prior art, the beneficial effects of the present invention are:
[0030] 1) This invention uses hydrothermal reaction throughout the process, without the need for high-temperature calcination or complex vapor deposition equipment, to synthesize a unique heterostructure and obtain ultrafine hollow CoSe2 nanoneedle material. This morphology has the advantages of simple preparation, low cost, high efficiency catalytic performance and excellent cycle stability in fields such as water electrolysis for hydrogen production.
[0031] 2) Compared to traditional loading methods, this invention breaks through the single morphology of traditional catalysts. Nanoneedles are directionally grown from a nickel foam substrate, forming a flower-like hierarchical structure. This retains the conductivity and structural stability of the three-dimensional porous framework of nickel foam while exposing more catalytic active sites through the high specific surface area of the hollow nanoneedles. In-situ growth eliminates binder resistance, improves electron conduction efficiency, and avoids catalyst agglomeration and detachment, thus enhancing structural stability. The mechanical strength of the nickel foam substrate, combined with the in-situ grown nanoneedle structure, endows the material with excellent cycle stability. Compared to traditional catalysts, this structure can resist current surges and bubble stripping during long-term electrocatalytic reactions, reducing the loss of active sites. Simultaneously, the self-supporting structure of the hollow nanoneedles prevents the accumulation of active components, continuously exposing fresh active sites and ensuring long-term stable catalytic performance.
[0032] 3) The method of this invention enables the reactants to react completely, and the microstructure of the catalyst can be controlled by changing the concentration of cobalt ions. 2+ with Se 2- The reaction proceeds fully, producing pure-phase CoSe2. At moderate concentrations, the highly efficient catalytic active center Co... 3+ With a proportion increasing to 40%-50%, the synergy between high-density nanoneedles and the complete hollow structure maximizes the number of active sites. At the same time, the hollow channels accelerate electrolyte penetration and bubble escape. The strong binding between the nanoneedles and the substrate, as well as the high conductivity of pure-phase CoSe2, reduce the charge transfer resistance (Rct).
[0033] 4) From a microscopic perspective, the ultrafine hollow CoSe2 nanoneedle material of this invention exhibits a large number of active groups such as hydroxyl groups on the surface of the nickel foam. Cobalt ions bind tightly to these groups through coordination, becoming nucleation sites for the CoSe2 nanoneedles. By adjusting the cobalt ion concentration, the bonding strength of this microscopic interface can be optimized. When the cobalt ion concentration is 2.9-3.1 mol / L, a stable anchoring structure is formed between the nanoneedles and the nickel foam support. From a microscopic morphology perspective, the connection between the nanoneedle root and the nickel foam surface is even tighter, with almost no gaps. This effectively avoids the problem of nanoneedles detaching from the support surface due to material volume changes during cycling, significantly improving the cycling stability of the material. In the microscopic path of electron transport, the excellent conductivity of nickel foam provides an efficient main channel for electron transport, while the microstructure of the hollow CoSe2 nanoneedles further shortens the branch distance of electron transport. Compared with solid nanostructures, the hollow tube walls greatly shorten the electron transport path from the support to the active sites on the nanoneedle surface, eliminating the need to penetrate the entire nanoparticle. Furthermore, variations in cobalt ion concentration affect the crystallization microstructure of CoSe2. Crystals formed at appropriate concentrations contain suitable oxygen vacancies or Se defects. These microscopic defects act as relay stations in the electron transport process, reducing resistance to electron migration and facilitating smoother electron transport within the material. In addition, this method of controlling the microstructure of hollow CoSe2 nanoneedles by regulating cobalt ion concentration offers significant advantages in synthesis. Different concentrations of cobalt ion solutions guide the nanoneedles to exhibit specific microscopic growth patterns. At low concentrations, cobalt ions diffuse slowly, naturally forming hollow structures through the Ostwald ripening mechanism, without the need for additional templates. At high concentrations, only the reaction time needs to be adjusted to control the length and thickness of the nanoneedles. This concentration-controlled synthesis method can stably and repeatedly produce materials with consistent microstructures, and the low cost of nickel foam lays the foundation for large-scale material production.
[0034] 5) Loading the CoSe2 active component onto the surface of nickel foam can not only effectively prevent the aggregation of the active component and improve its dispersibility, but also promote electron transfer and material diffusion through the three-dimensional porous structure of nickel foam, thereby significantly improving the overall performance of the catalyst. Attached Figure Description
[0035] Figure 1 The X-ray diffraction pattern of the ultrafine hollow CoSe2 nanoneedle material prepared in Example 1 of this invention;
[0036] Figure 2 This is a low-magnification scanning electron microscope image of the ultrafine hollow CoSe2 nanoneedle material prepared in Example 1 of the present invention;
[0037] Figure 3This is a high-magnification scanning electron microscope image of the ultrafine hollow CoSe2 nanoneedle material prepared in Example 1 of the present invention;
[0038] Figure 4 This is a low-magnification scanning electron microscope image of the ultrafine hollow CoSe2 nanoneedle material prepared in Comparative Example 1 of this invention;
[0039] Figure 5 This is a high-magnification scanning electron microscope image of the ultrafine hollow CoSe2 nanoneedle material prepared in Comparative Example 1 of this invention;
[0040] Figure 6 This is a low-magnification scanning electron microscope image of the CoSe2 material with nickel foam as a carrier prepared in Comparative Example 2 of this invention.
[0041] Figure 7 This is a high-magnification scanning electron microscope image of the CoSe2 material with nickel foam as a carrier prepared in Comparative Example 2 of this invention;
[0042] Figure 8 This is a comparison chart of the hydrogen evolution LSV curves of CoSe2 materials formed with different cobalt ion concentrations in Application Example 1 of this invention;
[0043] Figure 9 This is a comparison diagram of the Tafel slope of the hydrogen evolution environment of CoSe2 materials formed with different cobalt ion concentrations in Application Example 1 of this invention;
[0044] Figure 10 The application of this invention in Example 1, involving the formation of CoSe2 materials with different cobalt ion concentrations, and the hydrogen evolution reaction and double-layer capacitance (C... dl A comparison chart of related electrochemical activity values;
[0045] Figure 11 This is a comparison chart of oxygen evolution LSV curves of CoSe2 materials formed with different cobalt ion concentrations in Application Example 1 of this invention;
[0046] Figure 12 This is a comparison diagram of the Tafel slope of the oxygen evolution environment of CoSe2 materials formed with different cobalt ion concentrations in Application Example 1 of this invention;
[0047] Figure 13 The reaction of CoSe2 materials formed with different cobalt ion concentrations in Example 1 of this invention with oxygen evolution reaction and double-layer capacitance (C dl A comparison chart of related electrochemical activity values. Detailed Implementation
[0048] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0049] Example 1
[0050] A method for preparing ultrafine hollow CoSe2 nanoneedles includes the following steps;
[0051] 1) Pre-treat nickel foam with dimensions of 4 cm x 5 cm x 11 μm (length, width, thickness) by sonicating in deionized water for half an hour, then sonicating in alcohol for half an hour, repeating three times. Finally, place the nickel foam in a vacuum drying oven to dry at a temperature of 60 ℃ for 24 h, and then place the nickel foam vertically at the bottom of the reactor.
[0052] 2) Stir 3 mmol cobalt nitrate, 10 mmol urea and 4 mmol ammonium fluoride in 50 ml of water for 30 minutes; then transfer the above solution into a reaction vessel and keep it at 120 ℃ for 8 h; cool naturally to room temperature, wash with anhydrous ethanol and deionized water more than 3 times, and dry the prepared sample at 60 ℃ for 12 h.
[0053] 3) Dissolve 0.3 g selenium powder and 2 g sodium hydroxide in 50 ml deionized water, stir magnetically for 30 min, put into a reaction vessel, keep warm at 200 ℃ for 8 h, and cool naturally to room temperature to obtain an intermediate solution.
[0054] 4) Place the sample from step 2) into the liquid from step 3), then transfer it to a reaction vessel and keep it at 150 °C for 8 h. Allow it to cool naturally to room temperature, wash it more than 3 times with anhydrous ethanol and deionized water, and dry the prepared sample at 60 °C for 12 h to obtain CoSe2 hollow nanoneedle material, denoted as CoSe2-3.
[0055] All reagents used in the entire experiment were of analytical grade, with a purity of 99.99%.
[0056] The finished product obtained in Example 1 was subjected to X-ray inspection, and the results are shown in the figure. Figure 1 The presence of CoSe2 diffraction peaks indicates that CoSe2 was successfully prepared.
[0057] See Figure 2Low-magnification scanning electron microscope image of the hollow nanoneedle-composed nanoflower-like heterostructure electrode material reveals a nanoflower structure self-assembled by the hollow nanoneedles. The prepared material exhibits a large number of hollow nanoneedles, each growing uniformly. Figure 3 As shown, it exhibits a regular spherical flower cluster morphology, composed of a large number of neatly arranged hollow nanoneedles. The hollow nanoneedles have relatively uniform length and diameter, and grow radially from the center outward to form a highly ordered multi-level structure with an ultra-large specific surface area and uniform pore distribution, which is conducive to electrolyte penetration and gaseous product escape, and can fully expose catalytic active sites.
[0058] Example 2
[0059] A method for preparing ultrafine hollow CoSe2 nanoneedles includes the following steps;
[0060] 1) Pre-treat nickel foam with dimensions of 3 cm x 4 cm x 10 μm (length, width, thickness) by sonicating in deionized water for half an hour, then sonicating in alcohol for half an hour, repeating three times. Finally, place the nickel foam in a vacuum drying oven to dry at a temperature of 50 ℃ for 25 h, and then place the nickel foam vertically at the bottom of the reactor.
[0061] 2) Stir 2.9 mmol cobalt nitrate, 9.9 mmol urea and 3.9 mmol ammonium fluoride in 50 ml of water for 30 minutes; then transfer the above solution into a reaction vessel and keep it at 110 ℃ for 9 h; cool naturally to room temperature, wash with anhydrous ethanol and deionized water more than 3 times, and dry the prepared sample at 50 ℃ for 13 h.
[0062] 3) Dissolve 0.2 g selenium powder and 1.9 g sodium hydroxide in 50 ml deionized water, stir magnetically for 30 min, put into a reaction vessel, keep warm at 190 ℃ for 9 h, and cool naturally to room temperature to obtain an intermediate solution.
[0063] 4) Place the sample from step 2) into the liquid from step 3), then transfer it to a reaction vessel and keep it at 140 °C for 9 h. Allow it to cool naturally to room temperature, wash it more than 3 times with anhydrous ethanol and deionized water, and dry the prepared sample at 50 °C for 13 h to obtain CoSe2 hollow nanoneedle material.
[0064] All reagents used in the entire experiment were of analytical grade, with a purity of 99.99%.
[0065] Example 3
[0066] A method for preparing ultrafine hollow CoSe2 nanoneedles includes the following steps;
[0067] 1) Pre-treat nickel foam with dimensions of 5 cm x 6 cm x 12 μm (length, width, thickness) by sonicating in deionized water for half an hour, then sonicating in alcohol for half an hour, repeating three times. Finally, place the nickel foam in a vacuum drying oven to dry at a temperature of 70 ℃ for 23 h, and then place the nickel foam vertically at the bottom of the reactor.
[0068] 2) Stir 3.1 mmol cobalt nitrate, 10.1 mmol urea and 4.1 mmol ammonium fluoride in 50 ml of water for 30 minutes; then transfer the above solution into a reaction vessel and keep it at 130 °C for 7 h; cool naturally to room temperature, wash with anhydrous ethanol and deionized water more than 3 times, and dry the prepared sample at 70 °C for 11 h.
[0069] 3) Dissolve 0.4 g selenium powder and 2.1 g sodium hydroxide in 50 ml deionized water, stir magnetically for 30 min, put into a reaction vessel, keep warm at 210 ℃ for 7 h, and cool naturally to room temperature to obtain an intermediate solution.
[0070] 4) Place the sample from step 2) into the liquid from step 3), then transfer it to a reaction vessel and keep it at 160 °C for 7 h. Allow it to cool naturally to room temperature, wash it more than 3 times with anhydrous ethanol and deionized water, and dry the prepared sample at 70 °C for 11 h to obtain CoSe2 hollow nanoneedle material.
[0071] All reagents used in the entire experiment were of analytical grade, with a purity of 99.99%.
[0072] Comparative Example 1
[0073] A method for preparing CoSe2 material with nickel foam as carrier differs from Example 1 only in that the amount of cobalt nitrate is changed to 2 mmol, while the remaining steps and parameters are the same as in Example 1. The final product is denoted as CoSe2-2.
[0074] When the cobalt ion concentration decreased to 2 mmol, see Figure 4 and Figure 5 The material exhibits a relatively loose, sheet-like structure, which interweaves to form a network-like framework. Numerous slender nanoneedles extend outward from the edges of the sheets; however, the distribution of these nanoneedles is uneven, being denser in some areas and sparser in others. Simultaneously, the surface of the sheets is relatively rough, with irregular protrusions and depressions.
[0075] Comparative Example 2
[0076] A method for preparing CoSe2 material with nickel foam as carrier differs from Example 1 only in that the amount of cobalt nitrate is changed to 4 mmol, while the remaining steps and parameters are the same as in Example 1. The final product is denoted as CoSe2-4.
[0077] When the cobalt ion concentration is increased to 4 mmol, see Figure 6 and Figure 7 The morphology remains spherical, but compared to embodiment 1, the regularity of the spherical shape has decreased, and some aggregation has occurred, with some spherical structures sticking together. The number of nanoneedles has increased, making them appear more dense, and the uniformity of their length and diameter has deteriorated, with some exhibiting variations in length and thickness. Simultaneously, due to aggregation, the pore structure between the nanoneedles has become irregular, with some pores becoming blocked.
[0078] The structural differences between Comparative Examples 1-2 and Example 1 are attributed to the ionic synergistic effect between the metallic Co and Se elements. During the reaction, altering the concentration of cobalt ions effectively changed the original structural characteristics, resulting in the formation of a unique nanoflower heterostructure in the electrode material during hydrothermal synthesis. This synergistic effect accelerated charge transport, while the presence of three-dimensional hollow nanoneedles significantly increased the number of reactive sites. Therefore, the nanoflower-like heterostructure assembled based on hollow nanoneedles significantly improved the catalytic performance of the material.
[0079] Application Example 1
[0080] A method for producing hydrogen by electrolysis of water includes the following steps:
[0081] 1) Preparation of electrode materials: Electrode materials were prepared according to the methods described in Examples 1-3 and Comparative Examples 1-2, respectively, without the addition of other excipients.
[0082] 2) Electrode assembly: Using the electrode material prepared in step 1), as the working electrode, it is assembled with the reference electrode (Hg / HgO) and platinum sheet electrode to form a water electrolysis device. Ensure that the electrode material is uniformly distributed on the surface and effectively contacts the electrolyte.
[0083] 3) Water electrolysis reaction: Add 1M KOH electrolyte to the water electrolysis equipment prepared in step 2), and carry out the water electrolysis reaction under constant current or voltage. When an appropriate voltage or current is applied, water molecules decompose on the electrode surface through the electrolysis process, generating hydrogen and oxygen.
[0084] 4) Gas collection: Hydrogen and oxygen produced during electrolysis are separated and collected. Hydrogen is introduced into a storage device as a product, while oxygen is released.
[0085] 5) Hydrogen purification and storage: The obtained hydrogen can be further purified and stored as a clean energy source. Hydrogen produced using this method can be widely used in fuel cells, industrial hydrogen production, and other fields.
[0086] Electrocatalytic performance tests were conducted, and the comparison chart is shown below. Figure 8-13 As shown. The electrode material prepared in Example 1 exhibited excellent electrocatalytic performance. The required electrolyte for testing its electrochemical performance was 1 M KOH. In the hydrogen evolution reaction, a lower overpotential was required to achieve the same current density, indicating stronger catalytic activity and the ability to drive electrochemical reactions more efficiently. Figure 8 In the middle, at -50 mA·cm -2 At the specified current density, the overpotential of Example 1 was 217.7 mV, which was superior to Comparative Example 1 (235.7 mV) and Comparative Example 2 (228.7 mV). The Tafel slope further reflects the speed of the electrocatalytic reaction kinetics; the smaller the slope, the faster the reaction rate and the better the kinetics. Figure 9 As can be seen in Example 1, the slope of tafel is 126.18 mV·dec. -1 It still shows a comparison ratio of 1 (128.02 mV·dec) -1 ) and Comparative Example 2 (150.33 mV·dec -1 It exhibits superior kinetic performance, consistent with the promoting effect of material structure on catalytic reaction at a concentration of 3 mmol. Figure 10 The double-layer capacitors (C) of Example 1, Comparative Example 1, and Comparative Example 2 are shown. dl Comparison diagram, double-layer capacitance (C) dl C is positively correlated with the electrochemical active area. dl The larger the diameter, the larger the active surface area, exposing more catalytic active sites. Example 1C is shown in the figure. dl It is 0.31304 mF·cm -2 The concentration of active sites in Example 1 was significantly higher than the other two groups, further confirming that its active sites were more fully exposed. This matches the morphology of the hollow nanoneedles forming spherical flower clusters at 3 mmol, which is beneficial for the catalytic reaction. Similarly, in the oxygen evolution reaction, Example 1 was superior to the other two groups. At 50 mA·cm⁻¹ -2 At the given current density, the overpotential in Example 1 was 227.3 mV, and the Tafel slope was 35.43 mV·dec. -1 Furthermore, the oxygen evolution reaction of this material is related to the double-layer capacitance (C0). dl The relevant electrochemical activity value is 0.09961 mF·cm⁻¹. -2 This exhibits excellent electrochemical active surface area and outstanding reaction rate kinetics. With a cobalt ion concentration lower than that of the electrode material in Example 1, at 50 mA·cm⁻¹... -2At the given current density, the overpotential is 251.3 mV, and the Tafel slope is 54.92 mV·dec. -1 Double-layer capacitance (C dl The value is 0.08152 mF·cm. -2 The cobalt ion concentration of the electrode material was higher than that of Example 1 at 50 mA·cm⁻¹. -2 At the given current density, the overpotential is 242.3 mV, and the Tafel slope is 91.07 mV·dec. -1 Double-layer capacitance (C dl The value is 0.02702 mF·cm. -2 In summary, the CoSe2 material prepared with a cobalt ion concentration of 3 mmol exhibits the characteristics of the largest electrochemical active area, the fastest reaction kinetics, and the lowest overpotential. Its regular hollow nanoneedle self-assembled spherical flower cluster structure is the fundamental reason for its optimal performance.
[0087] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the structure of the present invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.
Claims
1. A method for preparing ultrafine hollow CoSe2 nanoneedles, characterized in that, Includes the following steps: (1) Mix and dissolve cobalt nitrate, urea and ammonium fluoride, put in nickel foam, keep warm at 110-130 ℃ for 7-9 h, cool to room temperature, take out the reacted nickel foam, wash and dry to obtain the precursor; (2) Mix and dissolve selenium powder and sodium hydroxide, keep warm at 190-210 ℃ for 7-9 h, and cool to room temperature to obtain an intermediate solution; (3) Place the precursor in the intermediate solution and keep it at 140-160 °C for 7-9 h. After cooling to room temperature, take out the reacted nickel foam, clean and dry it to obtain the ultrafine hollow CoSe2 nanoneedle material.
2. The method for preparing an ultrafine hollow CoSe2 nanoneedle material according to claim 1, characterized in that: In step (1), the nickel foam is cleaned and dried before being placed in the container. The cleaning is performed by ultrasonic treatment with deionized water and alcohol. The drying temperature is 50-70 ℃ and the drying time is 23-25 h. The nickel foam has a length of 3-5 cm, a width of 4-6 cm, and a thickness of 10-12 μm.
3. The method for preparing an ultrafine hollow CoSe2 nanoneedle material according to claim 1, characterized in that: All reactions were carried out in a reactor, with the nickel foam perpendicular to the bottom of the reactor.
4. The method for preparing an ultrafine hollow CoSe2 nanoneedle material according to claim 1, characterized in that: In step (1), the molar ratio of cobalt nitrate, urea, and ammonium fluoride is 2.9-3.1 : 9.9-10.1 : 3.9-4.
1.
5. The method for preparing an ultrafine hollow CoSe2 nanoneedle material according to claim 1, characterized in that: In step (1), the cleaning is carried out using anhydrous ethanol and deionized water, and the drying temperature is 50-70 ℃, and the drying time is 11-13 h.
6. The method for preparing an ultrafine hollow CoSe2 nanoneedle material according to claim 1, characterized in that: In step (2), the mass ratio of selenium powder to sodium hydroxide is 0.2-0.4: 1.9-2.
1.
7. The method for preparing an ultrafine hollow CoSe2 nanoneedle material according to claim 1, characterized in that: In step (3), the cleaning is carried out using anhydrous ethanol and deionized water, and the drying temperature is 50-70 ℃, and the drying time is 11-13 h.
8. An ultrafine hollow CoSe2 nanoneedle material prepared by a method according to any one of claims 1-7.
9. An electrode material, characterized in that: It was prepared using the ultrafine hollow CoSe2 nanoneedle material described in claim 8.
10. A method for producing hydrogen by electrolysis of water, characterized in that: The electrode material described in claim 9 is used as the working electrode.